Pengaruh Motivasi Dan Kompetensi Terhadap Kepuasan Kerja Di PT. Inti (Persero) Bandung - Asep Rochyadi Suherman (Majalah Bisnis & IPTEK, 2018)
In an organization, specifically the human resource department, high motivation and employee competency are essential to increase the employee satisfaction. This study aims to discover the effect of motivation and employee competency towards employee satisfaction. This study uses descriptive and verivicative method. The samples of this study are the employees of a company in Bandung. Moreover, this study uses the path analysis to know the direct and indirect impact. The results prove motivation and competency has significant effect to work satisfaction.